The Effect of Task-Based Language Teaching (TBLT) Approach in Developing Speaking Skill of the Eighth Grade Students of SMP Negeri 6 Watampone and Their Attitude Toward English - Gunawan Gunawan (LP3M Universitas Muhammadiyah Makassar)
Some students feel difficult when they have to speak in the classroom condition because there is always an audience. They feel so anxious in practicing their speaking skill in foreign language. The objectives of the research were to investigate the effect of using task-based language teaching (TBLT) approach in developing students’ speaking skill and to explore students’ attitude toward the use of task- based language teaching (TBLT) approach in teaching English speaking. Involving two classes as the experimental class and the control class which consisted of 60 students, selected by using Cluster Random Sampling technique. The research applied quasi-experimental method. The population of the research was the eighth grade students of SMP Negeri 6 Watampone in academic year 2015/2016.The data were collected through speaking test and questionnaires then analyzed by paired-sample t.test. The result of the research showed that (1) The use of task-based language teaching (TBLT) approach in teaching speaking significantly improved the students’ speaking skill. It was proved by the mean score of students’ posttest in experimental group was 70.00 and the mean score of students’ posttest in control group was 58.66. It means that the improvement of experimental group was higher than that of the control group. (2) The students’ attitude toward the use of task-based language teaching (TBLT) have strongly positive attitude. It was proved by the mean score of students’ attitude was 90%. It was categorized as strongly positive attitude.